Revitalization of Adab and Ethics in Elementary School Learning as an Effort to Strengthen the Pancasila Student Profile in the Digital Era - Johannes; Muhammadi; Enny Fitriani (International Journal of Educational Research Excellence, 2026)
The development of digital technology has brought significant changes to the field of education, including at the elementary level. Elementary school students now live in a digital ecosystem rich in information but lacking value filtering. This condition creates challenges in maintaining and instilling adab (proper conduct) and ethics in children. This study aims to analyze the urgency, strategies, and implementation of revitalizing adab and ethics in elementary school learning in the digital era. This research employs a descriptive qualitative method through literature studies and interviews with elementary school teachers at SD Negeri 060952 Medan Labuhan District. The research subjects consisted of nine classroom teachers, three principals, and eighteen students from grades IV–VI. Data were analyzed using reduction, data display, and conclusion drawing techniques based on the Miles & Huberman model. The results show a decline in students’ adab and ethics in three main aspects: (1) inappropriate communication behavior both directly and digitally, (2) low social awareness, and (3) weak discipline and learning responsibility. The dominant contributing factors include lack of parental supervision in technology use, limited integration of character education in learning, and the influence of permissive digital culture. The study also finds that revitalization can be implemented through integrating character values into thematic learning, teacher role modeling, and wise supervision of digital technology use. The conclusion emphasizes that education of adab and ethics must become the core spirit of the learning process in elementary schools, enabling students to use technology responsibly and ethically